Secreted MbovP0145 Promotes IL-8 Expression through Its Interactive β-Actin and MAPK Activation and Contributes to Neutrophil Migration - Doukun Lu; Hui Zhang; Yiqiu Zhang; Gang Zhao; Farhan Anwar Khan; Yingyu Chen; Changmin Hu; Liguo Yang; Huanchun Chen; Aizhen Guo (Pathogens, 2021)
Mycoplasma bovis (M. bovis) is an important pathogen of cattle responsible for huge economic losses in the dairy and beef industries worldwide. The proteins secreted by M. bovis are mainly related to its adhesion, invasion, virulence, and intracellular survival and play a role in mycoplasma–host interactions. In our previous study, we found MbovP0145, a secreted protein present in the M. bovis secretome, but little is known about its function. In this study, we assessed the inflammatory characteristics and underlined mechanism of this inflammation of recombinant MbovP0145 (rMbovP0145). For this, bovine lung epithelial cells (EBL) were stimulated by rMbovP0145 to see the IL-8 production in a time- and dose-dependent manner. We observed that rMbovP0145 increased the production of IL-8 via ERK1/2 and P38 pathway activation. Further, the effect of the M. bovis ΔMbov_0145 mutant and its complementary strain on IL-8 mRNA expression was also confirmed. A pulldown assay of the GST-tagged MbovP0145 protein with mass spectrometry demonstrated that β-actin could specifically interact with rMbovP0145 to mediate the IL-8 signaling. As knockdown of β-actin expression with RNA interference in EBL cells decreased the mRNA expression of IL-8 and the phosphorylated ERK1/2 and P38 proteins, whereas disrupted actin polymerization by cytochalasin D led to a significantly higher IL-8 expression and MAPK phosphorylation in rMbovP0145-stimulated cells. Compared to M. bovis HB0801 and its complementary strain, the culture supernatant of EBL cells infected with the M. bovis ΔMbov_0145 mutant induced less neutrophil migration to the lower chamber in a transwell system. In conclusion, MbovP0145 promoted IL-8 expression by interacting with β-actin through activation of the MAPK pathway, thus contributing to neutrophil migration.